Evaluation of Tear Evaporation Rate in Subjects with a High Body Mass Index - Abusharha, Ali; El-Hiti, Gamal A.; Alharbi, Abdulhadi; Fagehi, Raied; Alanazi, Mana A.; Alsaqar, Ali; Masmali, Ali M.; Almubrad, Turki (Klinische Monatsblätter für Augenheilkunde, 2022)
Aim This study evaluated the tear evaporation rate (TER) in subjects with a high body mass index (BMI) and tested the correlation between BMI and dry eye.Methods Thirty male subjects aged 18 – 38 years (26.4 ± 4.0 years) with a high BMI (26.4 – 47.0 kg/m2) were enrolled in the study. In addition, a control group of 30 males aged 20 – 36 years (24.0 ± 3.6 years) with a normal BMI (< 25 kg/m2) participated in the study for comparison. Each subject completed the ocular surface disease index (OSDI), followed by the TER measurement using a handheld VapoMeter.Results Significant differences (Wilcoxon test; p = 0.002 and 0.001) were found between the median scores of the OSDI (10.3 [3.7] vs. 5.9 [7.2]) and TER (35.5 [13.1] vs. 15.5 [12.8] g/m2 h) in the study and control groups, respectively. The OSDI indicated dry eye in 60.0% of subjects in the study group (n = 18). The TER measurements showed that 76.7% of subjects in the study group (n = 23) had dry eyes. A medium correlation (r = 0.569; p = 0.001) was found between the OSDI scores and TER measurements.Conclusions The means of the tear evaporation rate and the ocular surface disease index scores are significantly higher in subjects with a high BMI compared with the control group. Therefore, a high BMI is considered a risk factor for dry eye. The measurement of the tear evaporation rate using a handheld VapoMeter is a simple and rapid method to detect dry eyes in combination with other tools.
Keywords: tear evaporation rate; high body mass index; dry eye; handheld VapoMeter; tear film evaporation